SIMILE Widgets: Timeline. Version 2.3. App. - GRUMBACH, ELIZABETH (Renaissance & Reformation / Renaissance et Réforme, 2019)
The article reports on the open source software version for semantic interoperability "SIMILE Timeline" an embeddable system that can be placed within a larger project or single web page.